2017
DOI: 10.1055/s-0036-1588562
|View full text |Cite
|
Sign up to set email alerts
|

Regioselectivity of Mercury-Promoted Oxacyclizations of Alkynyl Diols

Abstract: Supporting InformationS-3 II. Synthesis of diynyl triol (S,S)-6Preparation of (±)-8: HgCl 2 (90 mg; 0.33 mmol) and Mg 0 (3.65 g; 150 mmol) were added to a two-neck oven-dried 250 mL round bottom flask equipped with reflux condenser. A solution of propargyl bromide (0.4 mL) in Et 2 O (16 mL) was added. The resulting suspension was heated gently with a heating gun to initiate the reaction, resulting in bubbling which persisted after heating ceased. The flask was then cooled to 0 °C, before dropwise addition of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The structural elucidation of the corresponding acetate derivative 224 was possible through NMR spectroscopy, including COSY, HMBC, HMQC and NOESY correlations of the protons at the C-O-C portion of the oxocane ring. 175 (R)-9-Hydroxypentadecan-3-one (R)-225 underwent a diastereoselective reductive cyclization mediated by Et 3 SiH and TMSOTf in dichloromethane to furnish exclusively the cyclic eight-membered ether (−)-cis-lauthisan 95. Similarly (S)-9hydroxypentadecan-4-one (S)-225 produced (+)-isolaurepan 191 (Scheme 35).…”
Section: Scheme 26 Scheme 27mentioning
confidence: 99%
“…The structural elucidation of the corresponding acetate derivative 224 was possible through NMR spectroscopy, including COSY, HMBC, HMQC and NOESY correlations of the protons at the C-O-C portion of the oxocane ring. 175 (R)-9-Hydroxypentadecan-3-one (R)-225 underwent a diastereoselective reductive cyclization mediated by Et 3 SiH and TMSOTf in dichloromethane to furnish exclusively the cyclic eight-membered ether (−)-cis-lauthisan 95. Similarly (S)-9hydroxypentadecan-4-one (S)-225 produced (+)-isolaurepan 191 (Scheme 35).…”
Section: Scheme 26 Scheme 27mentioning
confidence: 99%
“…Interestingly when 1.4-dihydroxy-5-alkyne derivatives were subjected to a Hg(OTf) 2 -catalyzed cyclization then oxacyclization takes place to form tetrahydropyran derivatives ( Scheme 43 ) [ 101 ]. Later it was shown that alkynyl diol 150 when treated with 20 mol % Hg(OTf) 2 followed by Et 3 SiH afforded bispyranoyl ketone 151 , but when Hg(OTf) 2 was increased (1 equiv) then fused pyran-oxocane derivative 152 was isolated [ 102 ].…”
Section: Reviewmentioning
confidence: 99%
“…The amino group and two hydroxyl groups in its molecule can be modified by simple steps. According to the literature investigation, chloramphenicol base derivatives as catalysts show good activity and selectivity in many organic reactions 31–35 . The rigidity of the chloramphenicol base can be increased by replacing the hydrogen on the amino group with a cycloalkyl group to give ligands 2a and 2b (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature investigation, chloramphenicol base derivatives as catalysts show good activity and selectivity in many organic reactions. [31][32][33][34][35] The rigidity of the chloramphenicol base can be increased by replacing the hydrogen on the amino group with a cycloalkyl group to give ligands 2a and 2b (Scheme 1). In addition, the nitro group in the structure of chloramphenicol base has a strong electron-withdrawing ability, and it may reduce the electron cloud density on the amino group, resulting in a decrease in the coordination ability of the nitrogen atom to zinc, which may affect its catalytic properties.…”
mentioning
confidence: 99%